The inhalation effect of Osmanthus fragrans var. Aurantiacus on physiological parameters in chronically stressed rats - Moon Yeon Youn; Jin-Ju Cho; Seong Jun Hong; Seong Min Jo; Hyangyeon Jeong; Sojeong Yoon; Younglan Ban; Hyeonjin Park; Jae Kyeom Kim; Young Jun Kim; Eui-Cheol Shin (Food Chemistry: X, 2024)
This study evaluated the effects of inhaling Osmanthus fragrans var. aurantiacus (OFA) extracts in Sprague-Dawley (SD) rats experiencing chronic stress. Rats were exposed to restraint stress or circadian disruption and were inhaled either distilled water or OFA extracts. Electronic nose (E-nose) analysis identified 35 volatile aromatic compounds (VACs) in OFA extracts. Chronic stress led to a decrease in body weight initially, serotonin concentration, and the weights of the liver, kidneys, and fat pads. Additionally, circadian disruption increased melatonin levels and decreased cholesterol concentrations. Inhalation of OFA increased dietary intake during the early phase and restored the tissue weights that have changed by chronic stress. Furthermore, it led to an increase in melatonin levels and changes in cholesterol levels. Taken together, our results indicate that OFA inhalation improves physiological changes caused by chronic stress through regulating dietary intake, restoring tissue weights, and modulating hormone and cholesterol levels.